ANALISIS MINIMISASI LIMBAH PADAT MEDIS DI RS PB - Elnovrian Purnama Saghita; - Thamrin; Dedi Afandi (Sistem Informasi, 2017)
This research was conducted between February and April 2016 and is housed in RS PB. This study aims to analyze the medical solid waste minimization. The method used is survey method with qualitative descriptive research. Based on this research, medical solid waste minimization efforts that have been done of medical waste segregation, House keeping, preventive maintenance, and management of materials, while only limited efforts to use waste reuse (reuse). Recycling (recycle) and recovery (recovery) of medical waste has not done RS PB. Based on 2004 and 1204 Kepmenkes PP 18 jo 85, 1999, sorting and storage of medical waste is not eligible.